A168 UTILITY OF FOLLOW-UP PANCOLONIC DYE SPRAY CHROMOENDOSCOPY FOR THE DETECTION AND TREATMENT OF DYSPLASTIC LESIONS IDENTIFIED DURING HIGH-DEFINITION WHITE-LIGHT ENDOSCOPY IN PATIENTS WITH COLONIC INFLAMMATORY BOWEL DISEASE. (21st February 2022) - Dziegielewski, C; Gupta, S; McCurdy, J; Sy, R; Saloojee, N; Murthy, S
Abstract: Background: Patients with inflammatory bowel disease (IBD) involving the colorectum are at higher risk for the development of flat and poorly delineated dysplastic lesions. Pancolonic dye spray chromoendoscopy (DCE) can represent an adjunct to white light endoscopy (WLE) that enhances detection and delineation of such lesions. Aims: We evaluated the utility of follow-up DCE for lesion detection and treatment in patients with IBD who had visible (polypoid or flat lesions) or invisible (identified in non-targeted biopsies) dysplasia detected during high-definition (HD)-WLE. Methods: We retrospectively studied patients with colonic IBD from The Ottawa Hospital who underwent DCE by a trained endoscopist, as follow-up for dysplasia detected during HD-WLE, over a 7-year time period (2013–2020). We collected demographic and disease-specific variables. Results: Twenty-four patients were included (mean age 56.7±13.8 years, 50.0% male, 70.8% ulcerative colitis, mean disease duration 18.0±11.0 years, 70.8% moderate or severe disease activity historically, and 41.7% remote history of dysplasia). Seventeen (70.8%) patients were referred following detection of invisible dysplasia; the remainder (29.2%) were referred for surveillance of poorly defined visible dysplastic lesions. For those referred following detection of invisible dysplasia, DCE identified visible dysplasia at the same site in 8/17 (47.1%) patients, at a different site in 6/17 (35.3%) patients, and no dysplasia in 3/17 (17.6%) patients. DCE identified 1.39±1.50 new visible dysplastic lesions per patient that were not identified on index HD-WLE. DCE upgraded the highest grade of dysplasia and diagnosed colorectal cancer in 2/24 (8.3%) patients, which was missed on index HD-WLE. Endoscopic resection was successful in 23/34 (76.7%) dysplastic lesions identified on DCE. However, DCE was unable to facilitate lesion resection in three patients due to advanced lesion characteristics. Follow-up data was available for 17/24 (70.8%) patients (mean 0.88±0.58 years). Of these patients, 7/17 (41.2%) developed subsequent dysplasia, including 4/17 (23.5%) at a site of prior invisible dysplasia, 2/17 (11.8%) at sites of prior visible dysplasia, and 1/17 (5.88%) at a different site. One of these patients developed high-grade dysplasia requiring resection. Conclusions: In this study, DCE is a valuable tool for dysplasia detection and treatment in persons with colonic IBD who have ill-defined dysplasia identified during HD-WLE. Given some patients developed dysplasia following DCE in our cohort, it is important to maintain close follow-up and obtain biopsies around sites of prior invisible and visible dysplasia. Further studies are required to validate our findings. Funding Agencies: None